HISTOLOGICAL STUDY OF ERYTHROID LINEAGE IN THE BONE MARROW OF LOCAL ADULT GOAT (Caprus Hircus) - D. Hamdi, Y. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was conducted to investigate the normal maturation process of erythriod lineage in bone marrow of adult Iraqi goat. Five healthy adult male goats aged 26-34 months were chosen for this study. A simple technique used for obtaining marrow from goats, employs sedation xylazine hydrochloride 0.1 mg/kg body weight. Skin incision was made over the iliac crest. Marrow was aspirated with a syringe and smears were made directly. Erythropoiesis in the bone marrow of an adult goat included a successive morphological alteration resulting in production of erythrocytes. The lineage of erythroid of bone marrow of adult goat comprises; Rubriblast , Prorubricytes, Rubricytes, Metarubricytes, and Reticulocyte. The final cellular lineage of the erythropoiesis bone marrow of the goat was the formation of non-nucleated erythrocytes.